2019
DOI: 10.1101/658179
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A rule-based data-informed cellular consensus map of the human mononuclear phagocyte cell space

Abstract: Highlights  Defining a consensus of the human myeloid cell compartment in peripheral blood  3 monocytes subsets, pDC, cDC1, DC2, DC3 and precursor DC make up the compartment  Distinguish myeloid cell compartment from other cell spaces, e.g. the NK cell space 5  Providing a generalizable method for building consensus maps for the life sciences 4 Abstract Single-cell genomic techniques are opening new avenues to understand the basic units of life.Large international efforts, such as those to derive a Human C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 44 publications
2
19
0
Order By: Relevance
“…Nevertheless, the frequency of these cells is very low and supplementary studies are needed to fully understand their biological relevance. Moreover, two recent studies showed that one of these four subsets was a contamination by NK cells (92,93).…”
Section: Location and Characterizationmentioning
confidence: 99%
“…Nevertheless, the frequency of these cells is very low and supplementary studies are needed to fully understand their biological relevance. Moreover, two recent studies showed that one of these four subsets was a contamination by NK cells (92,93).…”
Section: Location and Characterizationmentioning
confidence: 99%
“…With the development of multi-dimensional single-cell techniques, assessment at the single-cell transcriptome level unexpectedly suggested 4 monocyte subsets in healthy volunteers; classical, non-classical, and 2 monocyte subsets, one expressing genes involved in cell cycle, differentiation and trafficking and the other being associated with a NK cell-like signature (15). By generating new single-cell transcriptomics data we now have evidence that the latter monocyte subset was due to misclassification of a particular subset of NK cells, indicating that the current model with 3 major subsets is still valid (16).…”
Section: Introductionmentioning
confidence: 98%
“…Finally, a role for the SLAN + subset of non-classical monocytes in TNF overproduction in viraemic HIV-infected patients was proposed, suggesting that they might be considered as a major actor in the immune hyperactivation of the disease (41). While SLAN seems to delineate a subset of non-classical monocytes, there is no evidence for transcriptional differences between SLAN + and SLAN − cells (16) which requires further work to understand the reasons for the discrepancy between homogeneity at the transcriptional, but heterogeneity at the protein level.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, by combining index sorting and high-content single-cell RNA-sequencing, we show further evidence that Slan expression does not reflect different cell subsets as the underlying overall transcriptional program is not different between Slan high and Slan low cells. Moreover, we clearly show that Slan+ cells are all non-classical monocytes (125).…”
Section: High-dimensional Approaches Shape the Myeloid Cell Spacementioning
confidence: 68%
“…We defined cell types and subsets by a combination of function, phenotype and transcriptional profile, which lead to the identification of precursors (pre-cDCs) for the cDC1 and cDC2 subsets in addition to the three main DC subsets (5). To reconcile these two major initial reports, we developed a strategy that allows developing cell type classification consensus based on phenotypic and transcriptional features also including prior knowledge (125). This approach revealed that (1) the AXL + Siglec6 + DCs (AS-DCs) described by Villani et al are mainly pre-cDCs as described in (5), (2) Mono4 are contaminating CD56 dim NK cells, and (3) cells introduced as CD16 + CSF1-R + CTSS + DCs are not belonging to the DC lineage.…”
Section: High-dimensional Approaches Shape the Myeloid Cell Spacementioning
confidence: 99%